Free boundary equilibrium in 3D tokamaks with toroidal rotation. (22nd May 2015) - Cooper, W.A.; Brunetti, D.; Faustin, J.M.; Graves, J.P.; Pfefferlé, D.; Raghunathan, M.; Sauter, O.; Tran, T.M.; Chapman, I.T.; Ham, C.J.; Aiba, N.
Abstract: The three-dimensional VMEC equilibrium solver has been adapted to numerically investigate the approximate toroidal rotation model we have derived. We concentrate our applications on the simulation of JET snakes and MAST long-lived modes under free boundary conditions. Helical core solutions are triggered when 〈 β 〉 exceeds a threshold value, typically 2.7% in JET-like plasmas. A large plasma current and edge bootstrap current can drive helical core formations at arbitrarily small 〈 β 〉 in which the ideal saturated internal kink coexists with an ideal saturated external kink structure of opposite phase. The centrifugal force linked with the rotation has the effect of displacing the plasma column away from the major axis, but does not alter significantly the magnitude of the edge corrugation of the plasma. Error field correction coil currents in JET-like configurations increase the outer midplane distortions by 2 cm. The edge bootstrap current enhances the edge modulation of the plasma driven by the core snake deformations in MAST.